Effects and mechanisms of APP and its cleavage product Aβ in the comorbidity of sarcopenia and Alzheimer’s disease - Wu, Jiale; Tang, Jun; Huang, Di; Wang, Yu; Zhou, Enyuan; Ru, Qin; Xu, Guodong; Chen, Lin; Wu, Yuxiang (Frontiers in Aging Neuroscience, 2024)
Sarcopenia and AD are both classic degenerative diseases, and there is growing epidemiological evidence of their comorbidity with aging; however, the mechanisms underlying the biology of their commonality have not yet been thoroughly investigated. APP is a membrane protein that is expressed in tissues and is expressed not only in the nervous system but also in the NMJ and muscle. Deposition of its proteolytic cleavage product, Aβ, has been described as a central component of AD pathogenesis. Recent studies have shown that excessive accumulation and aberrant expression of APP in muscle lead to pathological muscle lesions, but the pathogenic mechanism by which APP and its proteolytic cleavage products act in skeletal muscle is less well understood. By summarizing and analyzing the literature concerning the role, pathogenicity and pathological mechanisms of APP and its cleavage products in the nervous system and muscles, we aimed to explore the intrinsic pathological mechanisms of myocerebral comorbidities and to provide new perspectives and theoretical foundations for the prevention and treatment of AD and sarcopenia comorbidities.